Numerical analysis of divertor target heat load of I-modes in comparison with H-modes of EAST. (1st March 2023) - Wang, Min; Wang, Xiaogang; Liu, Zixi; Yang, Xiaoyi; Zhou, Tianchun; Si, Hang; Shen, Chao
Abstract: Due to substantial edge transport of particles, I-mode operations offer a high potential for divertor heat load mitigation. In this work, the divertor parameters of I-mode operations on EAST have been investigated using the SOLPS-ITER code, and comparison with H-mode operations has also been made by modeling the I- and H-mode operation processes on EAST. The simulation shows that, for the same separatrix electron density at the outer midplane (OMP) n e, OMP sep, the upstream electron density of the I-mode is higher than that of the H-mode with no density pedestal, while the upstream temperature of the I-mode is almost the same as that of the H-mode with a temperature pedestal similar to that of the H-mode. As a combined result, the temperature and energy flux peaks of the I-mode are thus lower than those of the H-mode at the divertor target. Further parameter scanning investigation reveals that, under low-density conditions ( n e, OMP sep = 1.16 × 10 19   m − 3 ), the peak energy flow at the target is reduced by ∼34.1%, in the case of the I-mode as compared to the H-mode, while the peak target temperature is dropped by ∼54.6%. Under high-density conditions ( n e, OMP sep = 4.04 × 10 19   m − 3 ), on the other hand, the energy flux and temperature peaks are weakened by ∼28% and ∼30.1%, respectively. The upstream density at detachment onset of an I-mode is also lower than that of an H-mode, by 18.5%. These results suggest that I-mode operation is more appropriate for divertor heat load mitigation than H-mode operation.